Political Perspectives Towards the Unemployed in Nepal: A Class Based Study - Aryal, Ananta; Suwal, Bhim Raj; Adhikari, Keshav Prasad (State, Society and Development: PMPD Perspectives, 2025)
This study reorients the analysis of unemployment in Nepal from conventional market-driven perspectives to a class-based framework, examining how guiding political ideologies, party constitutions, and manifestos conceptualize the unemployed. Employing a qualitative research design, it uses thematic and textual analysis of foundational documents from five major political parties, alongside political ideologies such as people’s multiparty democracy, democratic socialism, and Marxism-Leninism-Maoism. Traditional paradigms of social stratification prioritize economic status, material wealth, and roles in production, often marginalizing the unemployed. In Nepal, this marginalization is further intensified by entrenched class and caste hierarchies, structural political-economic conditions, and psychosocial vulnerabilities. The findings reveal a persistent lack of recognition of the unemployed as a distinct social class within both political discourse and ideological frameworks. While foundational ideologies historically emphasized state-led economic models, employment generation, land redistribution, and labor empowerment, current policy practices indicate a shift toward neoliberalism—marked by market oriented reforms, privatization, foreign investment, and increasing reliance on remittance economies. Despite rhetorical commitments to job creation and skill development, implementation remains inconsistent and inadequate. Consequences include persistent youth unemployment, rural neglect, rising foreign labor migration, and the growth of informal labor markets. Political documents frequently reference the working class and other social groups, yet the unemployed are rarely acknowledged. This invisibility exacerbates inequality and fosters latent class antagonism, as the unemployed remain excluded from welfare, training, and political representation. The study argues that unemployment in Nepal should be understood as a structural and political phenomenon, requiring a class-sensitive framework and inclusive, accountable governance.